Electrochemical Synthesis of Nanocrystalline Ni-Pd Alloys in Alkaline Ni2+ – Pd2+ – Cl− – NH3 – H2O System and Their Catalytic Activity towards Water Splitting Process. Issue 9 (1st January 2017) - Mech, K.; Chopart, J. P.; Wróbel, M.; Żabiński, P.; Szaciłowski, K.
Abstract : Reported results concerning electrochemical co-deposition of nickel with palladium in Ni 2+ – Pd 2+ – Cl − – NH3 – H2 O system. Obtained results indicated possibilities of synthesis of alloys of wide composition range, from 6.1 to 83.7 at. % of Pd. Electrodeposition of Ni-Pd alloys in the system was reported for the first time. Concentration of Pd in coatings was significantly higher than it was reported for Ni-Pd alloys deposited from sulfate-ethylenediamine and chloride electrolytes. Crystallite size of resulted alloys was definitely lower than reported in the literature. XRD analysis indicated that crystallites of electrodeposited alloys are of the diameter of few nanometers. Electrochemical tests reveal that simultaneous reduction of [Pd(NH3 )4 ] 2+ and [Ni(NH3 )x (H2 O)6-x ] 2+ complexes taking place at potentials more electronegative than ca. –0.5 V. Alloys were investigated toward their applications as catalyst for water splitting in alkaline sodium hydroxide solution. Observed Tafel slope amounting from 93 to 222 mV dec −1 indicated that in each case rate determining step (RDS) is water molecules reduction reaction.